Application of Project Based Learning Methods to Increase the Activeness and Creativity of Class XI TKJ Students: Penerapan Metode Pembelajaran Project Based Learning Untuk Meningkatkan Keaktifan dan Kreatifitas Siswa Kelas XI TKJ - Ibnu Sudarmadi (Perkumpulan Doktor Indonesia Maju (PDIM), 2023)
The characteristic of modern education today is the emphasis on students' active and creative participation, which includes intellectual and emotional aspects in the learning process. In the context of learning graphic printing skills, the focus is on developing students' operational capacity, both mentally and physically. However, observations and interviews at SMK Negeri 7 Sijunjung show that learning needs to be more varied. Some teachers teach using conventional methods, such as games, demonstrations, and videos, while students follow the teacher's instructions without being actively and creatively involved. This makes learning less attractive for students as an alternative to increasing student engagement. This research was conducted through two cycles, each involving planning, implementing actions, observing, and reflecting. The action was carried out by utilizing internet media and other information technology and giving students project assignments. The research results showed an increase in students' average activity and creativity from one meeting to the next at the end of the second cycle. This indicates that the use of the project-based learning model can increase student involvement, and this model can be applied to help students develop their respective competencies.